2021
DOI: 10.3390/insects12040319
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characteristics of Fat Body Protein 1 in the Oriental Fruit Fly, Bactrocera dorsalis

Abstract: Bactrocera dorsails fat body protein 1 (Bdfbp1) cDNA was cloned (GenBank accession no. MT514270), and the complete 3,749-bp cDNA encoded a 1,152-amino acid protein. The phylogenetic relationship of dipteran fbp1s was analyzed. The sequence XP_028900815 from the insect genome project for Zeugodacus cucurbitae (LOC105219342) was proposed that two fbp1 genes were present in the sequence. The developmental transcriptional expression profiles were determined. In the larval stages, Bdfbp1 mRNA had significantly high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…dorsalis from various perspectives, while those on fat body of B. dorsalis were still rare events. , …”
Section: Introductionmentioning
confidence: 99%
“…dorsalis from various perspectives, while those on fat body of B. dorsalis were still rare events. , …”
Section: Introductionmentioning
confidence: 99%
“…Fat bodies ll the body cavity especially in the abdominal region (Chapman 2013), and the development of fat body is a characteristic process, especially in diapausing insects. Although fat body function has been extensively studied, fat body polymorphisms have mainly been unstudied, although it has been observed that adults of the Oriental fruit y Bactrocera dorsalis (Hendel) have two types of fat body (Yu et al 2021). Also, in two lepidopteran species, two types of fat body have been identi ed that have different structures and functions (Haunerland and Shirk 1995); Larvae of the Indian meal moth Plodia interpunctella (Hubner), (Shirk and Malore 1989) and the corn earworm Helicoverpa zea (Boddie), (Haunerland et al 1990; Wang and Haunerland 1992) have two types of fat bodies, while adults have only a single type of fat body.…”
Section: Introductionmentioning
confidence: 99%